Experimental and clinical tests of FDA-approved kinase inhibitors for the treatment of neurological disorders (update 2024) - Hassan Aliashrafzadeh; Dewey Liu; Samantha De Alba; Imad Akbar; Austin Lui; Jordan Vanleuven; Ryan Martin; Zhang Wang; Da Zhi Liu (Exploration of Drug Science)
Since our previous summary of the 74 FDA-approved kinase inhibitors in clinical and preclinical trials for non-cancerous neurological treatment, the US FDA has approved 13 additional kinase inhibitors since early 2022. This update incorporates new evidence for the now 87 FDA-approved kinase inhibitors in clinical and preclinical trials for the treatment of non-cancerous neurological disorders. By the end of October 2024, nearly all 87 FDA-approved kinase inhibitors have been tested in various animal models of non-cancerous neurological disorders, with twenty entered into clinical trials and six used for off-label treatments of neurological conditions in humans. Considering the challenges posed by intellectual property (IP), legal considerations, and limited blood-brain barrier (BBB) permeability, which may restrict some FDA-approved kinase inhibitors from effectively targeting the central nervous system (CNS), we further discuss the feasibility of designing novel proprietary analogs with enhanced BBB penetration to improve their therapeutic potential in neurological disorders. The new drugs typically retain full IP rights and remain costly; while repurposing kinase inhibitors may provide effective and affordable treatments for non-cancerous neurological disorders.